2000
DOI: 10.1186/cc688
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The benefit of albumin administration in the critically ill patient is unproven. Epidemiological evidence suggests that there is an increase in death among patients with burns, hypoalbuminaemia, and hypotension treated with human albumin solution (HAS). In critical illness, hypoalbuminaemia is a result of transcapillary leak, decreased synthesis, large volume body fluid losses and dilution caused by fluid resuscitation. When treating patients with hypoalbuminaemia, efforts must be centred around correction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Serum albumin is involved in a number of physiologic functions: regulation of plasma oncotic pressure (providing up to 65%–75% of normal colloid oncotic pressure) and capillary permeability, compound transport, and free radical scavenging [12, 13]. In critical illness, hypoalbuminemia is a function of loss due to vascular permeability, dilution with fluid resuscitation, and decreased albumin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum albumin is involved in a number of physiologic functions: regulation of plasma oncotic pressure (providing up to 65%–75% of normal colloid oncotic pressure) and capillary permeability, compound transport, and free radical scavenging [12, 13]. In critical illness, hypoalbuminemia is a function of loss due to vascular permeability, dilution with fluid resuscitation, and decreased albumin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that albumin replacement therapy did not decrease the rates of death or major complications [20,21]. However, others found that treatment of hypoalbuminemic patients with exogenous human albumin solution resulted in a greater than twofold decrease in major complications [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…All of these results indicate the importance of nutrition management in reducing the incidence of postoperative complications. However, simply albumin replacement therapy with exogenous human albumin solution did not decrease the rates of death or major complications, probably as the underlying etiology of hypoalbuminemia is not solved and exogenous albumin is rapidly degraded [ 20 , 42 ], so an integrated management of nutritional support to improve the serum albumin level and nutritional and physiological stabilization of patients is necessary.…”
Section: Discussionmentioning
confidence: 99%